Le jardin comme dispositif de vision du temps - Aline Gheysens (Projets de Paysage)
This paper proposes to consider the garden as a spatial system giving rise to an intimacy experience of vision and retranscription of time. That exploratory study is illustrated by the case of La Petite Escalère, a sculpture park located at the French Basque country. Using previous studies about space and time, it is shown that this spatial system can be compared with an autobiographical writing practice. That exploration relies on the fact that, in the case of the owner of the garden, literary and garden spaces, which were designed and layed out simultaneously, are deeply interconnected.